Rapid cycling bipolar disorders in primary and tertiary care treated patients - Hajek, Tomas; Hahn, Margaret; Slaney, Claire; Garnham, Julie; Green, Joshua; Růžičková, Martina; Zvolský, Peter; Alda, Martin (Bipolar disorders, 2008)
Objective:  Rapid cycling (RC) affects 13–30% of bipolar patients. Most of the data regarding RC have been obtained in tertiary care research centers. Generalizability of these findings to primary care populations is thus questionable. We examined clinical and demographic factors associated with RC in both primary and tertiary care treated populations. Method:  Clinical data were obtained by interview from 240 bipolar I disorder (BDI) or bipolar II disorder (BDII) community‐treated patients and by chart reviews from 119 bipolar patients treated at an outpatient clinic of a teaching hospital. Results:  Lifetime history of rapid cycling was present in 33.3% and 26.9% of patients from the primary and tertiary care samples, respectively. Among community‐treated patients, lifetime history of RC was significantly associated with history of suicidal behavior and higher body mass index. There was a trend for association between RC and BDII, psychiatric comorbidity, diabetes mellitus, as well as lower age of onset of mania/hypomania. In the tertiary care treated sample there was a trend for association between lifetime history of RC and suicidal behavior. Tertiary versus primary care treated subjects with lifetime history of RC demonstrated markedly lower response to mood stabilizers. Conclusions:  Lifetime history of RC is highly prevalent in both primary and tertiary settings. Even primary care treated subjects with lifetime history of RC seem to suffer from a more complicated and less treatment‐responsive variant of bipolar disorder. Our findings further suggest relatively good generalizability of data from tertiary to primary care settings.